Using agential morphogenesis to track professional identity development in higher education - Nudelman, Gabrielle (Critical Studies in Teaching and Learning, 2023)
Professional identity development (PID) is a growing focus for higher education researchers interested in graduate employability and workplace readiness. This raises the challenge of how to trace students’ identity shifts. This paper shows how Margaret Archer’s agential morphogenesis can be used to generate understandings of how students’ identities change during professional degree programmes. Archer’s theories of double and triple morphogenesis are applied to data collected through interviews and documentary research. The findings are presented as narratives about two final-year electrical engineering students who participated in employability-development focussed courses at a South African university. These narratives offer in-depth descriptions of the students’ identity shifts as they neared completion of their studies. The richness of the findings, which incorporate the constraints and enablements of the students’ professional identity development, leads to the paper’s argument that agential morphogenesis is a productive analytical tool for researchers wanting to better understand PID in higher education.